Information System Design Reminder Inventory Control At PT Nuansa Timur Lestari - Saputro, Janu Ilham; Hasibuan, Irfan Yuanda; Octavia, Dwiana (APTISI Transactions on Management (ATM), 2020)
The current information needs in the business world to be very important in determining the progress of a company. A good activity on a single company or technology is also determined by the available information. PT Lestari Eastern Nuances is a company engaged in the restaurant. The logging system supplies the raw materials of food are running currently still using Microsoft Excel to record incoming and outgoingraw food. The current running system still has many flaws and weaknesses as it takes quite a long time to figure out the amount of supplies of goods raw materials because an admin shed have to calculate the physical stock quantities directly, the occurrence of the difference in the number of requests the raw material with raw material expenses due to miscalculations by admin warehouse, takes a long time to make a request and expense report raw materials causing the company's performance be hampered, the absence of a reminder to remind Admins about the number of warehouse stock of raw materials so that when the raw materials needed by the chef stock no. Based on existing problems then needed a system to help the admin staff stock in managing demand and pengerluaran raw material so that it doesn't happen the difference in stocks of raw materials. The system will be created using the PHP programming language and the Mysql database, the method of analysis PIECES and using a systems development method in System Development Life Cycle (SDLC).